The language contact phenomenon in Thailand: English borrowing, comprehension, and public attitudes - Whanchit, Wararat; Sukkaew, Nootchanat (Universitas Syiah Kuala, 2023)
As the English lexicon has become more frequently borrowed and used in Thai mass media and social media, Thais are quickly adapting to such foreignness and are open to language contact-induced change. The current study explores the extent of the publics familiarity with borrowed words in contemporary Thai public media and attitudes toward language borrowing. The study participants comprised 120 Thais who voluntarily completed a questionnaire. They were from different age groups and were relatively highly educated. The instrument for the data collection was an online three-part questionnaire probing demographic information, an individuals comprehension of the borrowed lexicon as tested via 15 questions of lexical borrowing in context, and personal views probed in the questionnaire questions about English lexical borrowing. Follow-up interviews with six selected respondents according to age groups verified and elicited attitudes toward lexical borrowing. The findings revealed that high exposure to English resulted in a high level of comprehension, especially when words were transcribed in the Thai script with tone markers. If the borrowing was in Romanized script, it was less likely to be understood. The majority of the respondents recognized the need for English language borrowing in Thai communication, especially for terminology. They also expressed positive views toward the adoption of the practice. English was perceived as necessary for effective Thai communication, particularly among acquaintances and professionals. The ubiquity of English in Thai society today has led to general adaptability and acceptance of borrowing as part of language evolution; such practices are no longer a sign of prestige. The study suggests that language classrooms should consider using borrowed English lexicons to assist Thai EFL learners in developing English proficiency.